Nephroprotective potential of glucagon-like peptide-1 receptor agonists - Minara S. Shamkhalova (Endocrinology Research Centre, 2020)
Patients with diabetes mellitus (DM), which is a key factor in the development of kidney diseases, are increasingly competing for limited healthcare resources. Diabetic kidney disease (DKD) remains a significant cause of end-stage renal failure in the patients of many countries and is also associated with a high risk of cardiovascular pathology and mortality. The variety of clinical phenotypes of DKD in patients with type 2 diabetes mellitus (DM2) occurring due to a variety of pathogenetic factors and the characteristics of the evolution of complications under the influence of contemporary therapeutic methods, has been a special subject of discussion in recent years. Optimal control of the level of glycaemia and hypertension and timely blockade of the renin–angiotensin–aldosterone system do not provide sufficient protection for the kidneys. Over the recent decade, the nephroprotective potential of a group of modern anti-hyperglycaemic agents, i.e., glucagon-like peptide 1 receptor agonists (GLP1 RA) has been actively discussed. GLP1 RA have proven to be quite effective in controlling glycaemia and metabolic syndrome components (weight, systolic blood pressure and lipid profile) and in significantly reducing the risk of the primary, three-component endpoint (major adverse cardiac events: cardiovascular death, nonfatal myocardial infarction and nonfatal stroke) according to large studies on cardiovascular safety. The renal effects of GLP1 RA are attributed to a wide range of direct and indirect effects of glucagon-like peptide-1 on renal structures and functions owing to their anti-inflammatory, anti-oxidant and anti-apoptotic properties.